Life after Joe: Politics and War in the West Midlands, 1914–1918. (2nd January 2017) - Cawood, Ian
Abstract : By considering the political effects of the First World War in the whole of the West Midlands (rather than just Birmingham or the Black Country), this article seeks to demonstrate that, although the political culture of the region shifted in terms of behaviours and priorities, many of the features of the late Victorian and Edwardian regional polity survived the 'deluge' of war. The region became less politically homogenous, however, as the pressures of the war and the political responses to these exposed significant differences between the rural counties, the Black Country and the Birmingham conurbation. It concludes that the future political direction of Britain was by no means decided by 1918 and that the electoral results of the first fully democratic election demonstrated that there were many possible alternative choices for a population keen to cement the perceived unity of Britain which was credited for winning the longest and bloodiest struggle since the British Civil Wars.